Challenges in Mechanics of Time-Dependent Materials, Volume 2 Proceedings of the 2018 Annual Conference on Experimental and Applied Mechanics - Arzoumanidis, Alex.; Silberstein, Meredith; Amirkhizi, Alireza; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Challenges in Mechanics of Time-Dependent Materials, Volume 2 of the Proceedings of the 2018 SEM Annual Conference& Exposition on Experimental and Applied Mechanics, the second volume of eight from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Experimental Mechanics, including papers in the following general technical research areas: Characterization Across Length Scales Extreme Environments & Environmental Effects Soft Materials Damage, fatigue and Fracture Inhomogeneities & Interfaces Viscoelasticity Research in Progress.
Chapter 1.Modified Hyper-viscoelastic Constitutive Model for Elastomeric Materials -- Chapter 2.Temperature Dependence of Statistical Static Strengths for Unidirectional CFRP with Various Carbon Fibers -- Chapter 3.Time-Temperature Mechanical Response of a PVA Dual Cross-Link Self-Healing Hydrogel -- Chapter 4.Dissipative Damage Theory for Strongly Time-Dependent Composite Materials -- Chapter 5.Understanding Creep-Fatigue Interaction in Fe-25Ni-20Cr (wt.%) Austenitic Stainless Steel -- Chapter 6.The Development of Time Dependent Constitutive Laws of Jujube Flesh -- Chapter 7.Time-Temperature Dependent Creep and Recovery behavior of MWCNTs-Polypropylene Nanocomposites -- Chapter 8.Comparison of Porcine Brain Tissue with Surrogate Materials in Quasi-Static Compression and Dynamic Mechanical Analysis -- Chapter 9.Modeling of Cavitation Erosion Resistance in Polymeric Materials Based on Strain Accumulation -- Chapter 10.Experimental Investigation of Dynamic Strain Aging in 304L Stainless Steel -- Chapter 11.A Case Study to Evaluate Live Load Distributions for Pre-stressed RC Bridge -- Chapter 12.Experimental Investigation of Segmental Post-tensioned Girders -- Chapter 13.Experimental and Numerical Evaluations of Live Load Distributions of Steel-Concrete Composite Bridge -- Chapter 14.Strain Rate Dependent FEM of Laser Shock Induced Residual Stress.
Keywords: Mechanics, Applied; Solids; Building materials; Materials -- Analysis; Mechanics; Solid Mechanics; Building Materials; Characterization and Analytical Technique; Classical Mechanics